Parenteral Nutrition-Associated Liver Disease: The Role of the Gut Microbiota - Cahova, Monika; Bratova, Miriam; Wohl, Petr (Nutrients, 2017)
Parenteral nutrition (PN) provides life-saving nutritional support in situations where caloric supply via the enteral route cannot cover the necessary needs of the organism. However, it does have serious adverse effects, including parenteral nutrition-associated liver disease (PNALD). The development of liver injury associated with PN is multifactorial, including non-specific intestine inflammation, compromised intestinal permeability, and barrier function associated with increased bacterial translocation, primary and secondary cholangitis, cholelithiasis, short bowel syndrome, disturbance of hepatobiliary circulation, lack of enteral nutrition, shortage of some nutrients (proteins, essential fatty acids, choline, glycine, taurine, carnitine, etc.), and toxicity of components within the nutrition mixture itself (glucose, phytosterols, manganese, aluminium, etc.). Recently, an increasing number of studies have provided evidence that some of these factors are directly or indirectly associated with microbial dysbiosis in the intestine. In this review, we focus on PN-induced changes in the taxonomic and functional composition of the microbiome. We also discuss immune cell and microbial crosstalk during parenteral nutrition, and the implications for the onset and progression of PNALD. Finally, we provide an overview of recent advances in the therapeutic utilisation of pro- and prebiotics for the mitigation of PN-associated liver complications.
Keywords: střeva; microbiota; gut-associated immune system; FXR signalling; lékové postižení jater; intestinal permeability; parenterální výživa; Gastrointestinal Microbiome; střevní mikroflóra; Animals; lidé; Humans; pre/probiotics; zvířata; bile acids; Parenteral Nutrition; Intestines; Parenteral nutrition; Chemical and Drug Induced Liver Injury; PNALD